The eyes don’t see what the mind doesn’t know: discovering monoclonal gammopathy of thrombotic or thrombocytopenic significance - Mannava, Anjali Srikanth; Addanki, Raja Narendra Divakar (International Journal of Research in Medical Sciences, 2023)
A new scientific advancement in the field of medicine has been made thanks to the collaboration between the university of Michigan health and mayo clinic. A previously undiscovered illness has been named Monoclonal Gammopathy of Thrombotic/Thrombocytopenic Significance (MGTS) as a result of thorough investigation and the convergence of facts. The ramifications of this discovery for medical professionals are considerable, and they may lead to a radical change in how we approach patient care, diagnosis, and treatment.